2013
DOI: 10.1515/gps-2013-0046
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid technology in biodiesel production

Abstract: Abstract:The synthesis of biodiesel has received attention as an alternative source of energy to decrease our dependence on petroleum-based fuels. The catalyzed processes present a series of limitations and drawbacks, among them the high energy required for complex purification and undesirable side reactions. Supercritical fluid (SCF) technology is being proved an efficient approach compared to traditional methods for preparing biodiesel. This review illustrates the advances, advantages, and drawbacks involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In methanol, the hydrogen bond network is broken under supercritical conditions, this reduction in hydrogen bonding will encourage a stronger direct nucleophilic attack by methanol on the carbonyl group. The dielectric constant of methanol also decreases at supercritical state and this will lead to an elevation in reaction rate [128]. Nevertheless, the selection of alcohol is vital for evaluating the cost and performance.…”
Section: Supercritical Fluid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In methanol, the hydrogen bond network is broken under supercritical conditions, this reduction in hydrogen bonding will encourage a stronger direct nucleophilic attack by methanol on the carbonyl group. The dielectric constant of methanol also decreases at supercritical state and this will lead to an elevation in reaction rate [128]. Nevertheless, the selection of alcohol is vital for evaluating the cost and performance.…”
Section: Supercritical Fluid Methodsmentioning
confidence: 99%
“…Besides, alcohol with higher or branched structure is able to produce fuels with better properties. The extra carbon atom provided by ethanol can slightly increase the heat content and cetane number [128].…”
Section: Supercritical Fluid Methodsmentioning
confidence: 99%
“…Biodiesel synthesis using WFO as feedstock is a challenging task as it typically contains some undesirable components, i.e., free fatty acids (FFA) and water (Jacobson et al, 2008). Several studies (Demirbas, 2009;Hoang et al, 2013) reported that the feedstock containing a significant amount of FFA and water may inhibit the transesterification process to optimize biodiesel production. This is because FFA would react with the catalyst to form soap and inhibit the separation of biodiesel from glycerol.…”
Section: Darwin Atmadian Pratama Mardhotillahmentioning
confidence: 99%
“…Likewise, this reaction has been studied over heterogeneous acid catalysts [68][69][70][71][72][73][74][75][76][77][78][79] as well as using lipases as biocatalysts, either in solvent-free systems [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] or in ionic liquids [98][99][100][101]. Furthermore, many other innovative technologies have also been applied, such as supercritical conditions [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]<...>…”
Section: Biodiesel-like Biofuels That Integrate Glycerol As Glycerol mentioning
confidence: 99%